Pengenalan dan pemahaman bahaya pencemaran limbah plastik pada perairan di Kampung Sungai Kayu Ara Kabupaten Siak - Muhammad Fauzi; Deni Efizon; Eni Sumiarsih; Windarti Windarti; Rusliadi Rusliadi; Iskandar Putra; Bintal Amin (Unri Conference Series: Community Engagement, 2019)
Plastic waste pollution in the land and the river continues to rise. Plastic waste including marine pollution and debris can menyebab disrupt aquatic ecosystems. However, hazards of plastic waste pollution in the waters are still poorly understood by the public, especially for the people of Kampung Sungai Kayu Ara. To give knowledge to people in Kampung Sungai Kayu Ara Sungai Siak Apit about the dangers of plastic waste pollution in the rivers and sea required educational activities. So that more people know and understand the dangers of plastic waste, the public needs to be educated and understanding through extension activities. Extension activities carried out in Kampung Sungai Kayu Ara in September - October 2017. Implementation of education using lecture and discussion of the material presented. Conducted outreach activities to broaden the public about the negative impact of plastic waste so as to reduce the environmental impact of plastic waste on the river and the sea. The results show that the public targeted activity seen appreciation in receiving education of the activities carried out, the participants begin to recognize and understand the material presented and an increase understanding and knowledge about the dangers of plastic waste pollution between 65-80%.